(3GdGYJHGQ aj fGSN GdMOjK hefShNgs - (3eMeO Hf ehSi Hf YKeGf GHf MGRe, CHh HcQ, Rjf GdOjf, GdeYQha HGdMGRej,J (B584 (3g` s ((3jhSa Hf GdMSjf Hf GdYLei s)
(3ChdgG (B:s
(3GdMeO ddg HGQF GdfYe hNGdb GdGfhGQ hGdXde CeG HYO aGYde habc Gddg hEjGfG Cf GdWdH ddMOjK GdPi gh efHY GdGMcGe hYdjg JHfi OYGFe GdGSdGe s
(3BNQgG (B:s
(3aEPG GWjY QShd dGdg Udi Gddg Ydjg hSde abO GWjY Gddg JYGdi HWGYg QShdg Udi Gddg Ydjg hSde JSdjekG eHGQckG BNQ GdLRA GdSGHY hHJeGeg Je LejY cJGH GdGYJHGQ ai GdfGSN hGdefShN ef GdMOjK hGdMeO ddg hMOg s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B117 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B64s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B97s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI aGJM (B(1111) s
Keywords: (3GdMOjK h GdeUWdMs